Mangroves as a Pillar of the Blue Economy: Potential and Challenges in Climate Change Mitigation - Ajeng Faizah Nijma Ilma; Rinny Apriliany Zakaria; Tri Wahyu Yuliani; Anandhiya Intan Prabandari (LP2M IAIN Palopo, 2026)
The significant increase in carbon dioxide emissions in Indonesia poses a major threat to the sustainability of natural ecosystems and the economic resilience of coastal communities. In response to this threat, the concept of the blue economy emerged as an approach that balances economic growth and ecosystem conservation. One of the important climate change mitigation efforts is the planting and cultivation of mangroves, which are known to have a high capacity to absorb and store carbon. This study aims to identify the potential and challenges of mangrove management in supporting the blue economy and climate change mitigation, with a focus on Kebumen Regency, Indonesia. Using quantitative approaches and Structural Equation Modeling (SEM-PLS), this study analyzes public perceptions of environmental sustainability, financial motivation, governance, community participation, cultural and social values, as well as environmental risks and their impact on people's intentions to support the blue economy. The results show that perceptions of environmental sustainability, financial motivation, and social culture have a significant influence on the intention to support the blue economy, but these influences are limited to contexts involving complex institutional and management factors. The intention to support the blue economy turns out to have a negative effect on blue economy outcomes, such as the quality of life of coastal communities and the preservation of coastal ecosystems, which shows that there are structural obstacles and uncertainties that need to be overcome to achieve more optimal results. This study suggests the importance of integrating economic, social, and environmental aspects in sustainable blue economy-based mangrove management.